The return of Ellie Black : a novel - Jean, Emiko (2024)
"Detective Chelsey Calhoun's life is turned upside down when she gets the call Ellie Black, a girl who disappeared years earlier, has resurfaced in the woods of Washington state--but Ellie's reappearance leaves Chelsey with more questions than answers. It's been twenty years since Detective Chelsey Calhoun's sister vanished when they were teenagers, and ever since she's been searching: for signs, for closure, for other missing girls. But happy endings are rare in Chelsey's line of work. Then a glimmer: local teenager Ellie Black, who disappeared without a trace two years earlier, has been found alive in the woods of Washington State. But something is not right with Ellie. She won't say where she's been, or who she's protecting, and it's up to Chelsey to find the answers. She needs to get to the bottom of what happened to Ellie: for herself, and for the memory of her sister, but mostly for the next girl who could be taken--and who, unlike Ellie, might never return. The debut thriller from New York Times bestselling author Emiko Jean, The Return of Ellie Black is both a feminist tour de force about the embers of hope that burn in the aftermath of tragedy and a twisty page-turner that will shock and surprise you right up until the final page"--
Keywords: Policewomen -- Fiction; Missing children -- Fiction; Sisters -- Fiction; Enfants disparus -- Romans, nouvelles, etc; Washington (State) -- Fiction; Suspense fiction; Thrillers (Fiction); Novels